Sources of resistance to anthracnose and angular leaf spot in common bean for Costa Rica. - Araya, Rodolfo; Mora, Floribeth; Shingh, Shree P. (Agronomía Mesoamericana, 2006)
The objective of this study was to select sources of resistance to angular leaf spot and anthracnose from a diverse group of germplasm with known resistance to these diseases and other abiotic and biotic factors. Atotal of 173 common beans that included 46 landraces and 127 breeding lines were evaluated at two locations (Estación Experimental Fabio Baudrit Moreno and Sub-Estación Experimental Fraijanes, both of Universidad de Costa Rica) in 1996 and 1997. A mixture of four races (races 9, 10, 547, and 1024 of maximum virulence and coverage in Costa Rica) of the anthracnose pathogen was used to inoculate four times. Because of high natural incidence of angular leaf spot, inoculation was not necessary. Twenty-one landraces and 13 breeding lines were resistant (disease score of 3 or less) to antracnose. Only five landraces (G 12529, G 14934, G 19428, G 19696, and G 19831), one improved cultivar (ICA Tundama), and a breeding line UCR 55 had intermediate reaction (disease score between 4 and 6). Thus, for angular leaf spot evaluation of a much broader range of germplasm of common bean and other related species is suggested.